Examining Individual Characteristics and Program Performance to Understand Two-Year Recidivism Rates Among Drug Court Participants: Comparing Graduates and Terminators - Shannon, Lisa (International journal of offender therapy and comparative criminology, 2018)
Drug courts strive to break the cycle of substance use and crime by providing community-based treatment and rehabilitation. The purpose of the present study was to (a) identify significantly different factors between program participants (i.e., graduates/terminators) that may affect recidivism and (b) examine these significant individual and program performance factors associated with two-year recidivism. Secondary data were examined for a stratified random sample of drug court participants (N = 534). Examining any two-year post-program recidivism (defined as an arrest, conviction, or incarceration), over one third (37.6%) of graduates and almost all program terminators (95.3%) had two-year post-program recidivism (p < .001). For the overall sample, age, outpatient treatment, marital status, number of times treated for a psychiatric problem in a hospital, substance use (i.e., past-30-day cocaine use and intravenous opiate use), number of positive drug tests, and receiving any sanction/therapeutic response were associated with two-year post-program recidivism. Further analyses suggested age and outpatient treatment were particularly important for program graduates. Findings provide information for early targeting of resources to drug court participants most at risk of poorer post-program outcomes by identifying factors known at program entry and indicators during program participation.